2020
DOI: 10.3390/cells9041054
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biased Agonism at FPR1 as a Means to Encode Danger Sensing

Abstract: Ligand-based selectivity in signal transduction (biased signaling) is an emerging field of G protein-coupled receptor (GPCR) research and might allow the development of drugs with targeted activation profiles. Human formyl peptide receptor 1 (FPR1) is a GPCR that detects potentially hazardous states characterized by the appearance of N-formylated peptides that originate from either bacteria or mitochondria during tissue destruction; however, the receptor also responds to several non-formylated agonists from va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 63 publications
6
19
0
Order By: Relevance
“…Our finding that the ability of FPR1 agonists to trigger neutrophil migration is linked to the ability to recruit -arrestin is in agreement with the emerging concept of biased FPR agonism and functional selectivity shown to be valid also for FPR2. [29][30][31]45,68,69 Our data are also in line with the documented role of -arrestin in regulating cell migration in studies performed with other cell types, including neutrophillike HL60 cells. [70][71][72][73] At the structural level, these data suggest that is not reduced by a G q inhibitor, and this is in line with earlier studies that have identified the part of a G i containing G protein downstream of FPR1, to be the link between the receptor an activation of the PLC-PIP 2 -IP 3 -Ca 2+ pathway.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that the ability of FPR1 agonists to trigger neutrophil migration is linked to the ability to recruit -arrestin is in agreement with the emerging concept of biased FPR agonism and functional selectivity shown to be valid also for FPR2. [29][30][31]45,68,69 Our data are also in line with the documented role of -arrestin in regulating cell migration in studies performed with other cell types, including neutrophillike HL60 cells. [70][71][72][73] At the structural level, these data suggest that is not reduced by a G q inhibitor, and this is in line with earlier studies that have identified the part of a G i containing G protein downstream of FPR1, to be the link between the receptor an activation of the PLC-PIP 2 -IP 3 -Ca 2+ pathway.…”
Section: Discussionsupporting
confidence: 87%
“…30,31,79 FPR1 internalization has, however, also been sug-gested to be a G i-independent process. 68 but prime the PAF response. When it comes to the crosstalk between FPR1 and FFAR2, low concentrations of RE-04-001 could be primed by allosterically modulated FFAR2.…”
Section: Discussionmentioning
confidence: 95%
“…Complementing earlier in vivo studies administering recombinant AnxA1 [ 23 , 25 ], Anxa1 −/− mice displayed a boosted immune response characterized by an increased leucocyte migratory behaviour and a substantial resistance to the anti-inflammatory action of glucocorticoids in several acute inflammation models [ 24 ]. Mechanistically, in carrageenan-induced paw oedema and zymosan-induced peritonitis, the prominent ability of AnxA1 to counteract inflammatory events occured through binding of extracellular AnxA1 to formyl peptide receptors (FPRs), a family of G-protein coupled receptors found on many cells of the innate immune system, including neutrophils and monocytes [ 26 , 27 ]. The AnxA1/FPR2 axis inhibits neutrophil recruitment to sites of inflammation, a critical step in the regulation of inflammation [ 28 ].…”
Section: Anxa1mentioning
confidence: 99%
“…The cannabinoid receptors respond to both the exogenous phytocannabinoid D 9 -tetrahydrocannabinol as well as half a dozen en-docannabinoids (Felder and Glass, 1998;McPartland et al, 2006). Likewise, FPR1 is a proinflammatory danger-sensing GPCR that not only responds to pathogen-associated molecular patterns of foreign microbial and endogenous mitochondrial origin but also mediates anti-inflammatory effects when activated by the endogenous annexin A1 peptide Ac-2-26 (Gröper et al, 2020).…”
Section: Multiple Physiological Ligandsmentioning
confidence: 99%